Economic comparison of the monitoring programmes for bluetongue vectors in Austria and Switzerland. (2nd May 2015) - Pinior, B.; Brugger, K.; Köfer, J.; Schwermer, H.; Stockreiter, S.; Loitsch, A.; Rubel, F.
Abstract : With the bluetongue virus serotype 8 (BTV‐8) outbreak in 2006, vector monitoring programmes (according to EU regulation 1266/2007) were implemented by European countries to obtain information on the spatial distribution of vectors and the vector‐free period. This study investigates the vector monitoring programmes in Austria and Switzerland by performing a retrospective cost analysis for the period 2006–2010. Two types of costs were distinguished: costs financed directly via the national bluetongue programmes and costs contributed in‐kind by the responsible institutions and agricultural holdings. The total net costs of the monitoring programme in Austria amounted to €1, 415, 000, whereby in Switzerland the costs were valued at €94, 000. Both countries followed the legislation complying with requirements, but differed in regard to sampling frequency, number of trap sites and sampling strategy. Furthermore, the surface area of Austria is twice the area of Switzerland although the number of ruminants is almost the same in both countries. Thus, for comparison, the costs were normalised with regard to the sampling frequency and the number of trap sites. Resulting costs per trap sample comprised €164 for Austria and €48 for Switzerland. In both countries, around 50 per cent of the total costs can be attributed to payments in‐kind. The benefit of this study is twofold: first, veterinary authorities may use the results to improve the economic efficiency of future vector monitoring programmes. Second, the analysis of the payment in‐kind contribution is of great importance to public authorities as it makes the available resources visible and demonstrates how they have been used.